Heat Shock Alters Mesenchymal Stem Cell Identity and Induces Premature Senescence - Shimoni, Chen; Goldstein, Myah; Ribarski-Chorev, Ivana; Schauten, Iftach; Nir, Dana; Strauss, Carmit; Schlesinger, Sharon (Frontiers in Cell and Developmental Biology, 2020)
Sudden changes in environmental temperature, which are becoming frequent events, may have serious health consequences. A major question is how heat stress affects normal development and differentiation on both the cellular and the organism level. Here, we use an in vitro experimental system to address how heat shock treatment influences the properties of bovine mesenchymal stem cells (MSCs) - multipotent progenitor cells, which are found in most tissues. Since cattle are sensitive to harsh external temperatures, studying the effects of heat shock on MSC provides a unique platform to address cellular stress in a physiologically relevant model organism. Following isolation and characterization of MSCs from the cow’s umbilical cord, heat shock was induced, either as a pulse (1h) or continuously (3 days), and consequent effects on MSCs were characterized. heat shock induced extensive phenotypic changes in MSCs and dramatically curtailed their capacity to proliferate and differentiate. These changes were associated with a partial arrest in the G1/S or G2/M checkpoints. Furthermore, MSCs lost the ability to resolve the inflammatory response of RAW macrophages in co-culture. A possible explanation for this loss of function is the accumulation of ROS and malfunction of the mitochondria in the treated cells. Eventually, heat shock treatments resulted in stress-induced premature senescence, affecting MSCs abilities to properly proliferate for many passages to follow. In summary, exposure to elevated external temperatures leads to mitochondrial damage and oxidative stress which in turn conveys critical changes in the proliferation, differentiation and immunomodulatory phenotype of heat-stressed MSCs. Better understanding the effect of heat shock on humans and animals may result in important health and economic consequences.